THE EFFECT OF ANDROGEN DEPRIVATION THERAPY ON THE LIPID PROFILE AND BLOOD GLUCOSE LEVEL IN PROSTATE CANCER PATIENTS IN ADAM MALIK GENERAL HOSPITAL MEDAN - Irawan, Willi; Warli, Syah Mirsya (Indonesian Journal of Urology, 2017)
Objective: The aim of this study is to observe the effect of Androgen Deprivation Therapy (ADT) on patients with advanced stage of prostate cancer on the lipid profile and blood glucose level. Material & Methods: This is a descriptive cross-sectional study and include the prostate cancer patients which were admitted to Urology Policlinic in Haji Adam Malik General Hospital, Medan from June 2014 – June 2015 and also received ADT. Results: From June 2014 – June 2015, a total of 25 prostate cancer patients receiving ADT was included in this study with an average age of 67.08 ± 7.48 years old. The median prostate specific antigen (PSA) level of this group of patients is 19.6 ng/mL and the lowest and highest value of 3.4 and 278 ng/mL respectively. ADT administration is found to cause a significant elevation of 2-hour postprandial blood glucose (121.12 ± 21 mg/mL vs 134.64 ± 33.35 mg/mL, p-value=0.011) and Glycosylated hemoglobin (5 ± 0.5% vs 5.5 ± 0.79%, p-value=0.000) (HbA1c) after 6 months of therapy. Additionally, ADT administration within 3 and 6 months of duration had also significantly increased triglyceride (TG) level when compared to before treatment (104.4 ± 38.67 vs 131.2 ± 32.27 vs 127 ± 33.43 respectively, p-value=0.005). Conclusion: ADT treatment in prostate cancer patients increase triglyceride levels after 3 and 6 months of treatment followed by 2-hour postprandial blood glucose and HbA1C levels after 6 months of the treatment.